Stigma and Discrimination Among Professionals in Portuguese Integrated Continuing Care Units: Stigma and Discrimination in ICCUs - Rocha, Patrícia Castro; Sousa, Sara De; Marques, António; Simões De Almeida, Raquel; Trigueiro, Maria João; Campos, Filipa; Portugal, Paula (European Journal of Mental Health, 2024)
Introduction: Stigma surrounding mental illness (MI) poses a significant obstacle to treatment access, hinders recovery, and may lead to suboptimal care. Breaking the chains of prejudice and embracing tolerance are essential steps in fostering understanding and compassion for those living with MI. Aims: This study aims to describe the levels of stigma and discrimination against individuals suffering from MI among professionals in Portuguese Integrated Continuing Care Units (ICCUs). Methods: A quantitative, observational, cross-sectional study involving 163 participants utilized a sociodemographic questionnaire, alongside two assessment instruments – the Attribution Questionnaire (AQ-27) and Community Attitudes Toward Mental Illness (CAMI). Results: Results revealed significant differences in stigma levels based on education (pprejudice = .001; ptolerance = .007) and occupation (pprejudice = .025), higher stigma being associated with lower education levels and specific healthcare occupations (medical assistant). Additionally, a positive correlation was found between age and stigma perception (r = -236, pprejudice = .002; r = -167, ptolerance = .033). Conclusions: The findings underscore the urgent necessity for targeted anti-stigma interventions within Portuguese integrated continuing care units, focusing on mitigating education-based disparities, and addressing specific healthcare occupations that exhibit heightened stigma. Effectively combating stigma among professionals is crucial for fostering a more inclusive and compassionate environment in these care settings.